Implementasi Sistem Mudharabah sebagai Dasar Eksistensi dan Pengembangan Usaha Kerajinan Keset - Barory, Chulil (Dalwa Islamic Economic Studies: Jurnal Ekonomi Syariah, 2023)
This research is motivated by the district's strategic position as an area on the regional economic route in East Java, namely between Surabaya and Banyuwangi. Therefore, it stimulates the surrounding villages to develop in utilizing waste which can be processed into production materials that have economic value for village development. This is greatly supported by the jargon of Pasuruan Regency as a maslahat village. This research was conducted using a qualitative descriptive research method with data collection methods used namely observation, interviews, and documentation. The data analysis used is data reduction, data presentation, and conclusion drawing. In accordance with the results of research conducted that the implementation of the mudharabah contract is carried out in the development of a home industry for doormats with capital providers, namely 50: 50 with the risk of loss being borne by the home industry manager.